THE ESSENCE OF THE CONCEPT OF “PATRIOTISM” IN STUDENTS OF THE DIRECTION OF MILITARY EDUCATION UP TO THE CALL (American Journal of Interdisciplinary Research and Development, 2023)
Through this article, the formation of a civil duty, a sense of personal responsibility, a sense of belonging to the fate of the motherland, an active life position and a firm belief, professional skills in them by educating students of the direction of military education up to the call.